An interview study of Gift-giving in China at New Year - Zhang, Shuo (2007)
The purpose of this dissertation is to examine to what a extent the Chinese culture including the custom during Chinese New Year, reciprocity, face and Guanxi has influence on gift-giving among Chinese people and how these factors affect the behavior of gift-giving during Chinese New Year using qualitative research method with in-depth interview and limited observation. This dissertation stemmed from the observations of gift-giving in Bejing institute of geological engineering (BIGE) in China, where I was in the period of internship from January to June in 2006. The interpretation of my research about gift giving during Chinese New Year in China is mainly relied on textual data collected through in-depth interviews with 28 employees (12 males and 16 females) and also a little limited observation of them in the workplace. We highlighted the significance and limitations of our examination and analysis for gift-giving in China during New Year, both in the introduction and in the conclusion. Further recommendations and study areas are also proposed at the end of the paper